An Etrusco-Italic Antefix of Potnia Theron from Ardea - Suliman-Wolf, Hamutal (Archäologischer Anzeiger, 2024)
This article discusses an unpublished Etrusco-Italic terracotta antefix decorated with a Potnia Theron previously in the Etruscan collection at the Israel Museum, Jerusalem (today temporarily deposited at the Comando Carabinieri per la Tutela del Patrimonio Culturale in Rome). Based on the antefix’s technical description and interpretation, the author establishes that it belongs to a series of mould-made objects produced during the 3ʳᵈ century B.C. in Ardea, Latium. The Potnia Theron was depicted in Etruria and Central Italy from the 7ᵗʰ to the 1ˢᵗ century B.C. in various materials and on objects, such as jewellery, vases, and architectural elements like the antefix. Her image, distributed throughout all of Etruria and Central Italy, appeared in religious and public areas and represented a strong nature goddess laden with symbolic apotropaic powers.